Scrum method assessment in Federal Universities in Brazil: multiple case studies - Oliveira, Elton Rodrigues de; Ribeiro, Priscilla Cristina Cabral; Méxas, Mirian Picinini; Oliveira, Saulo Barbará de (Brazilian Journal of Operations & Production Management, 2023)
Goal: Assess the Agile Methodology Scrum in a software development project at Federal universities in the Southeast Brazil. Design / Methodology / Approach: The method in this paper is multiple case studies and a qualitative approach. The data collection was performed using a questionnaire with open and closed questions based on the constructs of the literature review. Six Federal universities were selected in two states in the Southeast Region, based on previous contacts with institutions, and the analysis unit was the Information of Technology Centers or the Superintendent of Information Technology. Results: It was noticed a low level of maturity in the use of agile methods in a great part of the universities and a high turnover of the team components, due to the scholarship students who participated in the research. In the open questions, it was noticed a very strong relationship between a set of subattributes: improvement in response time, cost and time reduction, increased of equipment performance and increase in added value. In the closed questions, it was noticed that Scrum had a better performance in the following sub-attribute samples: communication, collaboration, productivity, and time reduction. Limitations of the investigation: The number of interviewers in the universities, to provide deeper analysis for the case studies. Practical implications: The subattributes can be indicators to measure the performance of Scrum in corporations. Originality/Value: While previous studies focus on the application in large companies and in classes of Graduation Programs at universities, this paper focuses on administrative operations in the universities.